GLOBALIZATION AND ITS IMPACT ON ECONOMIC GROWTH: EVIDENCE FROM ASEAN COUNTRIES - Sardiyo Sardiyo; Martini Dhasman (Universitas Muhammadiyah Ponorogo, 2019)
The economic growth in ASEAN countries increases and develops in each year. globalization has a positive effect on economic growth through the effectiveness of the allocation of domestic resources, technological diffusion, increased productivity and capital. This study investigates globalization to economic growth in ASEAN in 2012-2017. The research method used judgmental sampling with samples of 11 countries. They were Brunei Darussalam, Cambodia, East Timor, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam. The analysis used path analysis to examine each variable. Globalization was determined by globalization index, economic globalization, social globalization, and politic globalization. Real Gross Domestic Product (GDP) and Gross Domestic Product (GDP) per capita are used as proxy for economic growth. The results describe that globalization had a significant positive association with economic growth. All indicators of globalization, show the positive association between globalization index, economic globalization, social globalization, and politic globalization to real Gross Domestic Product (GDP) and Gross Domestic Product (GDP) per capita. This confirms that globalization is able to provide a positive response in ASEAN.